Austro-German Provenance of the Organ Verses in the Archivo Musical de Chiquitos. (Revista Argentina de Musicología, 2014)
This article isn't available online.
Keywords: Jesuit Missions; Musical Archive of Chiquitos; Keyboard Music; Organ Verses